Association between non-invasive biomarkers and quality of life in Primary Sclerosing Cholangitis - Jingyu Dai; Emmanuel Selvaraj; Emma L. Culver; Adam Bailey; Michael Brady; Michael Pavlides; Jose Leal (PLoS ONE, 2025)
Background & aims Primary sclerosing cholangitis (PSC) is a rare chronic liver disease that impact quality of life (QoL). This study investigated the association between biomarkers of PSC disease severity and QoL. Methods Prospective study involving 80 participants with PSC at baseline and 55 at 1-year follow-up. QoL was assessed using patient reported outcomes (PROMs): RAND-SF36, SF6D and PSC-PRO. MRI-MRCP data was analysed using LiverMultiscan for iron-corrected liver T1 (cT1) and MRCP+ for the relative severity of intrahepatic biliary dilatations (RSIBD). Disease severity was also classified using FibroScan liver stiffness (LS), enhanced liver fibrosis (ELF), Mayo risk score (MRS), Amsterdam-Oxford model (AOM), alkaline phosphatase (ALP), presence of extrahepatic disease and dominant stricture (DS). Descriptive and regression analyses were conducted. Results At baseline, more advanced PSC was associated with differences in PROMs, AOM > 2, (PSC-PRO PSC symptoms, 5.181, p = 0.048), LS > 9.6 kPa (SF-6D, −0.081, p = 0.027), cT1 > 825ms (SF6D QoL, −0.161, p = 0.004; SF36 PCS, −10.595, p = 0.001; SF36 MCS, −10.726, p = 0.012), DS (PSC-PRO symptoms scores, 5.800, p = 0.025), RSIBD (SF-6D, −0.081, p = 0.016). During follow-up, increase in LS was associated with a reduction in QoL measured via SF-6D (−0.002, p < 0.001), SF36 physical component summary (−0.246, p < 0.001) and SF36 mental component summary (−0.171, p < 0.001). Conclusions QoL in PSC was associated with biomarkers of parenchymal liver fibrosis (LS, cT1), biliary disease (dominant strictures, RSIBD), and composite scores of disease severity (AOM). Increasing LS predicted further declines in QoL. Further research should explore MRCP+ metrics and their impact on QoL.